Porch lights [large type] - Frank, Dorothea Benton (HarperLuxe, 2012)
When Jimmy McMullen, a fireman with the NYFD, is killed in the line of duty, his wife, Jackie, and ten-year-old son, Charlie, are devastated. Charlie idolized his dad, and now the outgoing, curious boy has become quiet and reserved. Trusting in the healing power of family, Jackie decides to return to her childhood home on Sullivans Island. Crossing the bridge from the mainland, Jackie and Charlie enter a world full of wonder and magic--lush green and chocolate grasslands and dazzling red, orange, and magenta evening skies; the heady pungency of Lowcountry Pluff mud and fresh seafood on the grill; bare toes snuggled in warm sand and palmetto fronds swaying in gentle ocean winds.